Enhancing Students’ English Speaking Confidence through Game-Based Learning in an Indonesian Islamic Boarding School - Nuwailah Rochmah Rufqoti; Mutmainnah Mustofa (South Sulawesi Education Development (SSED), 2026)
Speaking is often perceived as one of the most challenging skills for EFL learners in Indonesian Islamic Boarding Schools (IBS), where limited opportunities for authentic practice and fear of making mistakes constrain students’ confidence and participation. This study aimed to enhance students’ speaking confidence and active participation through the integration of interactive games within a designated Language Area environment in a private Islamic Boarding School in East Java. The study employed a Classroom Action Research (CAR) design conducted in two cycles involving six female students. The intervention incorporated Word Chain and Guessing Game activities to create structured yet low-anxiety speaking opportunities. Data were collected through classroom observations, field notes, and students’ reflective questionnaires, and analyzed descriptively to trace changes in participation and perceived confidence across cycles. The findings indicate a progressive increase in students’ active engagement, rising from 50% participation in Cycle 1 to full participation in Cycle 2. Questionnaire responses further revealed reduced fear of making mistakes, increased willingness to speak, and positive perceptions of vocabulary recall during game-based activities. These findings directly address the research objective of fostering speaking confidence and participation within an IBS context. The study concludes that interactive games can serve as an effective pedagogical strategy to promote a supportive and low-anxiety speaking environment aligned with students’ daily institutional routines. However, the small sample size and short duration of implementation limit generalizability, suggesting the need for longitudinal studies examining sustained impacts on speaking proficiency.